ACTR-16. PERIPHERAL BLOOD CD4+ MONONUCLEAR CELL FRACTIONS ARE ASSOCIATED WITH OVERALL SURVIVAL AT FIRST RECURRENCE OF IDH-WILDTYPE GLIOBLASTOMA AFTER STANDARD CHEMORADIOTHERAPY: SECONDARY ANALYSES OF THE PHASE II DIRECTOR TRIAL. (5th November 2018) - Wirsching, Hans-Georg; Terksikh, Ekaterina; Silginer, Manuela; Krieg, Carsten; Tabatabai, Ghazaleh; Wick, Wolfgang; Reifenberger, Guido; Roth, Patrick; Becher, Burkhard; Weller, Michael
Abstract: The alkylating agent temozolomide prolongs survival of glioblastoma patients through induction of futile DNA mismatch repair in cancer cells. Whether systemic temozolomide effects on the immune system affect outcome has not been studied in detail. To address this question, we analyzed peripheral blood mononuclear cells (PBMC) of N=52 clinically well-annotated patients with recurrent, isocitrate dehydrogenase (IDH)-wildtype glioblastoma and of N=21 healthy donors by 11-color flow cytometry. Patients were treated within the randomized phase II trial DIRECTOR, which explored the efficacy of two dose-intensified temozolomide regimens at first recurrence of glioblastoma after standard chemoradiotherapy with first-line temozolomide. There were no efficacy differences between both dose-intensified temozolomide schedules in this trial. Unsupervised clustering of flow cytometry annotations identified two patient clusters, which differed in CD4+ T-cell fractions, but not with respect to CD8+ T-cells, CD4+;CD25+;FoxP3+ regulatory T-cells, B-cells or monocytes. All control samples clustered with the CD4high cluster. Patients in both clusters did not differ by age, gender, O6-methylguanine-DNA-methyl-transferase ( MGMT ) gene promoter methylation, tumor volume, Karnofsky performance score (KPS), number of first-line temozolomide cycles or steroid use. Progression-free survival was similar (CD4high vs CD4low 2.1 vs 2.4 months, p=0.19), whereas overall survival was longer in the CD4high cluster of patients (12.7 vs 8.7 months, p= 0.004). In a multivariate Cox model of overall survival that controlled for established prognostic factors, we found associations with overall survival for KPS (p=0.019), high CD4+ fractions (p=0.052) with relevant interactions with cluster assignment (p=0.058), residual tumor at study entry (p=0.068) and MGMT promoter methylation (p=0.072), but not age (p=0.96) or steroid use at study entry (p=0.32). There were no interactions of cluster assignment or CD4+ fractions with steroid use in this model. We conclude that temozolomide-associated CD4+ T-cell depletion may have unfavorable effects on the survival of glioblastoma patients, a finding that warrants further exploration.